ANALYSIS OF INTERNATIONAL TRADE LAW IN THE WORLD TRADE ORGANIZATION (CASE STUDY OF THE BAN ON THE EXPORT OF INDONESIAN NICKEL ORE TO THE EUROPEAN UNION) - Dodi Sugianto (Sean Institute, 2023)
In a lawsuit filed with the World Trade Organization (WTO) in November 2019, the European Union argued that the ban on exports of raw materials from Indonesia had unfairly harmed the stainless steel industry on the Blue Continent. Starting in the first quarter of 2020, the export of nickel ore is banned in Indonesia. The lawsuit was filed with the Dispute Settlement Body (DSB), because Indonesia was considered detrimental to the European Union's stainless steel industry and violated the provisions of Article X:1 GATT 1994, Article XI:1 GATT 1994, and Article 3.1(b) ASCM. Based on this background, the author wants to conduct research entitled